Investigation on the occurrence of heavy metals in bivalves: a comparison between moderately polluted and less polluted estuaries - Aswathi, C. (KUFOS, 2019)
Heavy metal pollution of the biosphere has dramatically accelerated since the start of the industrial revolution. The rapid pace of industrialization and urbanization has led to the problem of contamination with heavy metals. Aquatic ecosystems are constantly under the pressure of anthropogenic pollutants from different sources. Metals are introduced into the aquatic system as a result of weathering of soil and rocks, volcanic eruptions and from a variety of human activities involving mining, processing, agricultural, industrial and urban effluents and use of metals and substances containing metal contaminants. Metals such as Arsenic(As), Mercury(Hg), Cadmium(Cd), Copper(Cu), Chromium(Cr), Lead(Pb), Iron(Fe), Manganese(Mn), Zinc(Zn) etc.generally do not degrade; they therefore accumulate across the trophic chain. Accumulations in living organisms result in concentrations of several orders of magnitude higher than in surrounding water. Vembanad and Kavvayi backwaters are the two prominent lakes in Kerala that forms the lifeline of various floral and faunal resources. The concentration of heavy metals (Cu,Cd,andPb )were measured in water, sediment clam tissues and shells using Inductively Coupled Plasma-Optical Emission spectroscopy (ICP-OES). The study was conducted at different stations inVembanad and Kavvayi back watersand the samples were collected seasonally for a period of one year(June 2018 to April 2019). Results for the level in water were compared with EPA and KSPCB (Kerala State Pollution Control Board)water quality guidelines and it was found to be within the permissible limits. The mean level of heavy metals in the sediment (mg/kg) were in the order of Cu>Pb>Cd. The accumulation of metals in sediment were compared with USEPA, 1999 and the obtained metal concentration were found to be below the standard guideline. Comparisons were made of metal concentration in water and sediment with those in the tissues and shell of clams. It was found that there was metal accumulation in the clam tissues compared to water and sediments and the metal concentration in clams were below the permissible limit according to FSSAI. The results emerging from the present study indicate that the metal concentrations in water, sediment and clams were relatively low such that the metals do not cause any negative impacts to the aquatic ecosystem.